2022
DOI: 10.1101/2022.07.07.499061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

OpenCap: 3D human movement dynamics from smartphone videos

Abstract: Measures of human movement dynamics can predict outcomes like injury risk or musculoskeletal disease progression. However, these measures are rarely quantified in clinical practice due to the prohibitive cost, time, and expertise required. Here we present and validate OpenCap, an open-source platform for computing movement dynamics using videos captured from smartphones. OpenCap's web application enables users to collect synchronous videos and visualize movement data that is automatically processed in the clou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 109 publications
0
55
0
Order By: Relevance
“…Many studies have proposed portable-sensing methods to estimate knee kinematics (Table 2). Also, as previously mentioned, portable sensors coupled with neural networks and musculoskeletal simulation have shown promise at predicting knee kinetics [36, 81, 82]. Using these technologies to develop assessments that are fast and accurate enough for clinical deployment could enable better return-to-sport decision making and potentially lower the risk of reinjury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have proposed portable-sensing methods to estimate knee kinematics (Table 2). Also, as previously mentioned, portable sensors coupled with neural networks and musculoskeletal simulation have shown promise at predicting knee kinetics [36, 81, 82]. Using these technologies to develop assessments that are fast and accurate enough for clinical deployment could enable better return-to-sport decision making and potentially lower the risk of reinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Among these primary parameters, knee angles were estimated by many of the reviewed studies; however, only one included study estimated knee extension moment [36] and no study estimated knee abduction moment during jump-landing tasks or cutting. Recent research has shown that knee abduction moment during gait can be estimated from simulated 2-D video data using neural networks [81] or from real 2-D video data using neural networks and musculoskeletal simulation [82]. Future research should test these methods for dynamic activities relevant to ACL injury risk screening, such as jump-landing and cutting motions.…”
Section: Injury Risk Screeningmentioning
confidence: 99%
“…The information provided by the biomechanical analysis may be useful for return-to-sport decision-making and for informing the rehabilitation process but required more accessible technologies for wide clinical adaption. More accessible technologies are currently being developed, [see e.g., ( 39 )] but future work is needed to improve and validate the technologies to support their transfer to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although the GUI is more user friendly, it is neither open-source nor customizable. OpenCap (Uhlrich et al, 2022) has recently been released, and offers a user-friendly web application working with low-cost hardware. It predicts the coordinates of 43 anatomical markers from 20 triangulated keypoints, and imports them in OpenSim.…”
Section: Statement Of Needmentioning
confidence: 99%